Creep-Fatigue Response, failure mode and deformation mechanism of HAYNES 282 Ni based superalloy: Effect of dwell position and time. (June 2022) - Mukherjee, Shreya; Kumar Kar, Sujoy; Sivaprasad, S.; Tarafder, Soumitra; Viswanathan, G.B.; Fraser, H.L.
Graphical abstract: Highlights: Anisotropy in strain hardening causes C-F sensitivity with respect to dwell positions. Stress relaxation per cycle, strain energy density and C-F damage parameter correlate well with life. Inertia in increase in inelastic strain beyond the reversal point of imposed total strain. Fracture mode varies with dwell position and time. Deformation mechanism changes from shearing to Orowan looping as the dwell position changes. Abstract: Creep-fatigue (C-F) response of HAYNES-282 as a function of dwell position and time, along with corresponding deformation micro-mechanisms and failure modes are presented here. An inertia effect in inelastic strain beyond the total-strain reversal point is reported for the first time. Damage ( D C - F ) in the material is found to decrease in the order of both-dwell, compressive-dwell and tensile-dwell. D C - F, an effective stress relaxation per cycle and strain energy density are found to correlate well with life. A change in deformation mechanism from shearing to Orowan-looping explains the difference in damage as a function of dwell position. HAYNES 282 shows an inherent anisotropy in strain hardening behavior, being higher under compressive loading. We postulate that compressive dwell would be more damaging in such material, with dwell-time-softening nullifying the beneficial effect of strain hardening of the same segment. Failure occurs through a mixed-mode, with dominance of either transgranular or intergranular fracture, depending on dwell position and time.